Auditoría de gestión y su incidencia en el desarrollo de las actividades de la unidad administrativa de talento humano del distrito 12D06 Buena Fe – Valencia – educación, año 2017 - Bazurto Vergara, Suly Tamara (2018)
The present research work whose title is Audit of Management and its Incidence in the Development of the Activities of the Human Talent Administrative Unit of District 12D06 Buena Fe - Valencia - Education, Year 2017, facilities in which this study was conducted is located located in Buena Fe canton; in the streets Walter Roque and Ela Álava, the same one that was created by Ministerial decree 103 - 12 of January 25, 2012, through which integrates all public, private and fiscomisional educational institutions of all levels and modalities. The objective of this study was to evaluate the development of the activities of the Human Talent Administrative Unit of District 12D06 Buena Fe - Valencia - Education, using a Management Audit with the intention of improving its administrative processes, accompanied by the application of all research methods such as the historical method, inductive - deductive method and analytical method. With the application of the evaluation to the activities and functions carried out in District 12D06 Buena Fe - Valencia - Education, the level of confidence was moderate, represented with 56.67% and with a low level of risk represented with 43.33%. It is essential that the staff is aware of the objectives that the district seeks to achieve as an institution in order to carry out its activities successfully. .Keywords: Audit, resource management, human resources, administration, district.